2020
DOI: 10.1155/2020/3502981
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA RHPN1-AS1 Serves as a Sponge for miR-3133 Modulating the Cell Proliferation of Retinoblastoma through JAK2

Abstract: Purpose. To investigate the effects of lncRNA RHPN1-AS1 on retinoblastoma (RB) and further explore its underlying molecular mechanisms. Methods. The expression of RHPN1-AS1, miR-3133, (JAK2), and signal transducer and activator of transcription 3 (STAT3) was detected by qRT-PCR. CCK-8, EDU, and flow cytometry assays were conducted to assess the proliferation activity and apoptosis of RB cells. Double fluorescein and RNA immunoprecipitation assays were performed to detect the interaction between RHPN1-AS1 and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…To date, the role of miR-3133 in cancer has been poorly investigated, except in retinoblastoma and clear cell renal cell carcinoma. 45,46 In line with the above findings, our data indicate that miR-3133 plays a tumour-suppressive role in GIC. Previous studies have shown that miR-3133 is expressed at low levels in tumour tissues, but the mechanism of its downregulation remained unclear.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To date, the role of miR-3133 in cancer has been poorly investigated, except in retinoblastoma and clear cell renal cell carcinoma. 45,46 In line with the above findings, our data indicate that miR-3133 plays a tumour-suppressive role in GIC. Previous studies have shown that miR-3133 is expressed at low levels in tumour tissues, but the mechanism of its downregulation remained unclear.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that a newly discovered miRNA, named miR‐3133, is involved in the proliferation of GIC cells. To date, the role of miR‐3133 in cancer has been poorly investigated, except in retinoblastoma and clear cell renal cell carcinoma 45,46 . In line with the above findings, our data indicate that miR‐3133 plays a tumour‐suppressive role in GIC.…”
Section: Discussionsupporting
confidence: 87%
“…In retinoblastoma (RB) cells, RHPN1‐AS1 was upregulated. Silencing RHPN1‐AS1 inhibited the activity of RB cells and promoted apoptosis 31 . In our study, we found that expression of RHPN1‐AS1 markedly upregulated in PCa tissues and cells, silencing RHPN1‐AS1 inhibited proliferation and invasion, and induced apoptosis in PCa cells.…”
Section: Discussionsupporting
confidence: 50%
“…Overexpression of RHPN1-AS1 promoted proliferation and metastasis of EOC cells, knockdown of RHPN1-AS1 significantly inhibited the proliferation, migration and invasion of ovarian cancer cells. 11,30 In retinoblastoma (RB) cells, RHPN1-AS1 was 31 In our study, we found that expression of RHPN1-AS1 markedly upregulated in PCa tissues and cells, silencing RHPN1-AS1 inhibited proliferation and invasion, and induced apoptosis in PCa cells. Moreover, we found that overexpression of miR-7-5p or silencing EGFR induced PCa cell apoptosis.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, offsetting miR-3133-mediated JAK2/STAT3 inactivation aggravates RB. [35] Ribonucleotide reductase subunit M2 accelerates proliferation and EMT in RB through JAK2/STAT3. [36] As expected, this study revealed that SOCS3 was raised, and p-JAK2, p-STAT3 were decreased after miR-452-5p knockdown, while si-SOCS3 abolished these trends, implying that miR-452-5p might facilitate RB process through SOCS3/JAK2/STAT3.…”
Section: Interference With Mir-452-5p Represses Rb Tumor Growth Invas...mentioning
confidence: 99%